(untitled) (MAGNETON: Jurnal Inovasi Pembelajaran Fisika, 2026)
This study aims to analyze the effectiveness of integrating Basic Physics, Optics, and Electronics practicums through the STEM (Science, Technology, Engineering, and Mathematics) approach in improving the scientific literacy of students in the Physics Education Study Program at the University of Timor-Leste (UNTL). The practicums was a direct learning method that can help students understand physics concepts comprehensively. The low scientific literacy of students, indicated by an average pretest score of 45.2, is the main basis of this study. The method used is a quasi-experimental with a pretest-posttest control group design involving 68 second-semester students divided into an experimental group and a control group. The instrument used was a scientific literacy test based on PISA 2022 indicators consisting of 40 validated questions and an observation sheet for the implementation of STEM practicums. The results showed that the experimental group obtained an average posttest score of 78.6. The highest increase occurred in the scientific literacy dimensions of explaining phenomena scientifically at 38.4 and using data and evidence scientifically at 35.7. The integration of STEM through three practicums has been empirically proven to significantly increase the scientific literacy of UNTL Physics Education students.